FORMATION OF THE ADMINISTRATIVE MANAGEMENT SYSTEM OF ASSETS AND LIABILITIES OF A BANKING INSTITUTION IN THE STRATEGIC ASPECT (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the essence of the process of managing assets and liabilities of a banking institution. The works of ukrainian and foreign scientists devoted to issues of asset and liability management systems were studied and analyzed. The essence of the concept of the structure of assets and liabilities is determined. The main strategies for managing the bank's assets and liabilities have been identified - the asset management strategy, the liability management strategy, and the combined strategy.The purpose of the article is the formation of the formation of the system of administrative management of assets and liabilities of a banking institution. The main tasks of a comprehensive strategy and its important elements are defined. Two basic groups of asset and liability management methods are highlighted - methods of managing a certain risk and methods of modeling the optimal balance sheet structure. The shortcomings inherent in both groups were analyzed.It is proposed to use, in addition to classic digital methods, tools for influencing the structure of the bank's assets and liabilities. A diagram of the asset and liability management system from a functional point of view has been created. In order to effectively manage a banking institution, it is proposed to include digital tools for influencing the structure of assets and liabilities to the tools of the asset and liability management system in order to obtain maximum profit while maintaining reliability. For the formation of the MAL system, it is proposed to implement the following digital elements: implementation of the biometric system of online banking; integration with the Diya platform; distribution and promotion of the use of Visa pay-Wave cards; expansion and adaptation of POS lending (including biometric identification of the recipient) using POS terminals; expansion of online banking functionality. Their influence on the three main factors determining the degree of profit of a banking institution is determined.In the course of the analytical work, it was found that an important tool in the asset and liability management strategy is bank digitalization. Using digital technologies, banking institutions have the opportunity to reach a completely new level, providing innovative services and services to clients. Despite the fact that these directions have received active development in recent years, their potential has not yet been exhausted. The impact of digitalization provides significant benefits to banks and improves their attractiveness. This, in turn, provides stability to the banking institution and the ability to quickly adapt to unpredictable changes in the market. Thus, using digital tools as part of the formation of the asset and liability management system, it is possible to directly influence their structure and attract a larger number of customers, which directly affects the bank's profitability.
Keywords: system, bank, administrative management system, administrative management of assets and liabilities, strategic management of assets and liabilities, digital tools, online banking.